Adivasi studies: From a historian's perspective - Dasgupta, Sangeeta (History compass, 2018)
As adivasis become increasingly visible as subjects in debates around conversion, identity, indigeneity, and development, the field of "Adivasi Studies," centred on the subject of the adivasi, becomes increasingly relevant. As a newly emerging field, it engages with archaeology, anthropology, agrarian history, environmental history, subaltern studies, indigenous studies, aboriginal studies, and developmental economics but adds to these debates that are specific to the Indian context. This essay discusses some of the imperatives that make a revisit to the field of Adivasi Studies compelling. It engages with the ongoing dialogue amongst those who write the adivasis into the larger project of history-writing, and sets out the markers of the field of Adivasi Studies from a historian's perspective. It reflects as much some of the dilemmas that one faces while engaging with the field of Adivasi Studies.